2005
DOI: 10.1007/s00284-005-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CaENG1 Gene Encoding an Endo-1,3-β-Glucanase Involved in Cell Separation in Candida albicans

Abstract: The Candida albicans CaENG1 gene encoding an endo-1,3-beta-glucanase was cloned by screening a genomic library with a DNA probe obtained by polymerase chain reaction using synthetic oligonucleotides designed according to conserved regions found between two Saccharomyces cerevisiae endo-1,3-beta-glucanases (Eng1p and Eng2p). The gene contains a 3435-bp open reading frame (ORF), capable of encoding a protein of 1145 amino acids (124,157 Da), that contains no introns. Comparison of the ScEng1p sequence with parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
1
45
0
2
Order By: Relevance
“…Northern analysis of the ENG1 transcript showed a decrease in abundance 2.5 h into germination (96). Another study found that ENG1 and XOG1 expression increased during hyphal formation and that the increase was dependent on the serine/ threonine protein phosphatase Sit4p (transcriptional profiling [200]).…”
Section: Cell Wall-localized Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Northern analysis of the ENG1 transcript showed a decrease in abundance 2.5 h into germination (96). Another study found that ENG1 and XOG1 expression increased during hyphal formation and that the increase was dependent on the serine/ threonine protein phosphatase Sit4p (transcriptional profiling [200]).…”
Section: Cell Wall-localized Proteinsmentioning
confidence: 98%
“…It catalyzes the release of glucose from the nonreducing end. Eng1p had endoglucanase activity, as demonstrated by the release of reducing sugars from the substrate, and activity was specific for ␤-1,3-glucan (96). The eng1⌬/⌬ strain showed normal growth and morphogenesis.…”
Section: Cell Wall-localized Proteinsmentioning
confidence: 99%
“…Ace2 activates the expression of genes whose products are required for the controlled dissolution of the septum, such as the chitinase Cht3 or the endo-␤-1,3-glucanase Eng1 (Dunkler et al, 2005;Esteban et al, 2005) and several other genes, such as DSE1 (Mulhern et al, 2006). To determine whether Ace2-dependent transcription was activated in sep7⌬ hyphae, the expression of some Ace2-target genes was monitored by Northern blot.…”
Section: Deletion Of Sep7 Activates Cell Separation During Hyphal Growthmentioning
confidence: 99%
“…In C. albicans, three chitinase genes (CHT1, CHT2 and CHT3) have been cloned and it has been proposed that Cht2p has a similar function to ScCts1p (McCreath et al, 1995). It has also been shown recently that disruption of the ENG1 gene results in the formation of chains of cells (Esteban et al, 2005). To investigate whether the cell separation defect observed in cdc14⌬ mutants might be a result of a decrease in the transcription of these hydrolase genes, we analyzed the expression of CHT3 and ENG1 by northern blot.…”
Section: Journal Of Cell Science 119 (6)mentioning
confidence: 99%